The wish book Christmas - Austin, Lynn N. (Tyndale House Publishers, 2021)
"From the bestselling author of If I Were You comes a nostalgic and endearing holiday story that reminds us that sometimes, the most meaningful gifts are the ones we least expect and don't deserve. Best friends Audrey Barrett and Eve Dawson are looking forward to celebrating Christmas in postwar America, thrilled at the prospect of starting new traditions with their five-year-old sons. But when the Sears Christmas Wish Book arrives and the boys start obsessing over every toy in it, Audrey and Eve realize they must first teach them the true significance of the holiday. They begin by helping Bobby and Harry plan gifts of encouragement and service for those in their community, starting by walking an elderly neighbor's yellow lab-since a dog topped the boys' wish list for Santa. In the charming tale that follows, Audrey and Eve are surprised to find their own hearts healing from the tragedies of war and opening to the possibility of forgiveness and new love"--